2018
DOI: 10.18203/2394-6040.ijcmph20185079
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of allergy profile of patients visiting a tertiary care hospital in hilly areas of Himachal Pradesh

Abstract: Background: Allergic diseases are very common and are caused by allergen whose role varies according to climate changes. Not many studies are available regarding the same in our region. Skin prick test is a diagnostic procedure for allergy testing. The aim of the present study was to find out the seasonal variation of different allergies in our region.Methods: A total of 686 patients with allergic complaints were assessed for age and sex distribution, seasonal variation of number of allergy patients and season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Similar findings were noted in two Indian studies and a study conducted in western Iran [8,11,12]. The positive aspects of the domains of PRQLQ across age groups revealed mild affection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings were noted in two Indian studies and a study conducted in western Iran [8,11,12]. The positive aspects of the domains of PRQLQ across age groups revealed mild affection.…”
Section: Discussionsupporting
confidence: 87%
“…Asthma was the most common comorbidity observed in our study. A similar observation was reported which revealed that AR and Asthma control were directly proportional to each other [12]. Another interesting study showed AR findings in 58% of asthmatic children; however no association was established with asthma severity [13].…”
Section: Discussionsupporting
confidence: 71%
“…SPT is highly sensitive, specific, simple, inexpensive and reproducible investigation for diagnosis of allergic diseases. 6 The purpose of the study was to determine and characterize common allergens using SPT in patients of allergic rhinitis in a tertiary centre and hospitals of Saharanpur, India. The most common allergens found in our study were pollen (80%), dust (70%), mite(52%), insects(50%), fungi(48%) and epithelial antigen(20%).overall, pollen of Parthenium (70%) followed by house dust(64%) were found to be the most common offending allergens.…”
Section: Discussionmentioning
confidence: 99%
“…196 Sensitization Pattern. According to Nanda and Devi 197 , there is a pattern of sensitization to the allergens according to the seasons, as dust mite sensitization is maximum during winter months and rainy season and minimum during summer months. In contrast, pine mix sensitization is maximum during months of March to June.…”
Section: Q8 What Is the Importance Of Seasonal Variation In Respirato...mentioning
confidence: 99%
“…Additionally, the sensitization to allergens is most common in summer months as compared to winters. 197 Regarding seasonal variation, the maximum number of patients, sensitized is in summer months. In winters, many of the patients are of non-allergic rhinitis with the most common trigger being the cold climate.…”
Section: Q8 What Is the Importance Of Seasonal Variation In Respirato...mentioning
confidence: 99%